Practical applications of HR analytics a step-by-step guide - Banerjee, Pratyush; Pandey, Jatin; Gupta, Manish (Thousand Oaks SAGE, 2019)
In today's technology-driven world, HR analytics is pivotal to measure, express and take focused HR decisions. Practical Applications of HR Analytics equips readers with the required tools and techniques to effectively identify, capture and utilize the vast amount of available data in making better informed business decisions. The text is lucid and packed with practical illustrative examples, hands-on exercises and datasets. It is an invaluable resource for management students and HR professionals who want to translate the benefits of HR analytics into practice, thus paving the way for evidence-based human resource management. Key Features - Practical understanding of a range of open-source statistical GUI software - Focus on both descriptive and predictive analytics in HR - Chapter opening vignettes, industry examples and real-world case studies on application of HR analytics in organizations - Supplementary exercises and soft copy of datasets provided on Google Drive Link to facilitate hands-on training"--
Keywords: Personnel management -- Statistical methods